2013
DOI: 10.1098/rspb.2013.1225
|View full text |Cite
|
Sign up to set email alerts
|

Bigger mothers are better mothers: disentangling size-related prenatal and postnatal maternal effects

Abstract: Despite a vast literature on the factors controlling adult size, few studies have investigated how maternal size affects offspring size independent of direct genetic effects, thereby separating prenatal from postnatal influences. I used a novel experimental design that combined a cross-fostering approach with phenotypic manipulation of maternal body size that allowed me to disentangle prenatal and postnatal maternal effects. Using the burying beetle Nicrophorus vespilloides as model organism, I found that a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
139
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(153 citation statements)
references
References 62 publications
12
139
2
Order By: Relevance
“…We scanned the breeding boxes every hour using Vuescan professional edition software (Hamrick Software, Sunny Isles Beach, FL, USA) 170 until the eggs hatched. In accordance with previous studies, we defined a clutch as comprised of all eggs laid before the first larva hatched (Müller, 1987;Steiger, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…We scanned the breeding boxes every hour using Vuescan professional edition software (Hamrick Software, Sunny Isles Beach, FL, USA) 170 until the eggs hatched. In accordance with previous studies, we defined a clutch as comprised of all eggs laid before the first larva hatched (Müller, 1987;Steiger, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…As soon as the developing larvae reached their third instar, the mass of each larva within a brood was measured three times a day. Of each brood, some larvae were removed once they had achieved a mass of 70-120 mg (treatment group 'small') and transferred to a new container for pupation [37]. The remaining larvae were left with their parents and the carcass until the carrion was entirely consumed or the larvae left the carcass for pupation on their own (treatment group 'large').…”
Section: (Iv) Effect Of Body Size/nutritional Condition During Develomentioning
confidence: 99%
“…We manipulated the nutritional environment of the developing larvae which ultimately has an effect on adult body size [37]. Pairs of beetles were provided with a 20 g carcass (Mäu-Ra Farm, Radensleben, Germany) to initiate breeding.…”
Section: (Iv) Effect Of Body Size/nutritional Condition During Develomentioning
confidence: 99%
“…We have also shown that inbreeding depression in the offspring is less severe when the mother is present than when she is removed [12]. Given that small females provide less post-hatching care than large females [16,17], we hypothesized that inbred offspring would suffer a greater reduction in fitness (compared with outbred offspring) if they had a small mother than if they had a large mother. To test this hypothesis, we used a 2 Â 2 factorial design with the following treatment groups: (i) a large female with outbred offspring, (ii) a small female with outbred offspring, (iii) a large female with inbred offspring, and (iv) a small female with inbred offspring.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is still unknown whether such a buffering effect depends on the mother's phenotype. Maternal condition may affect the quantity or quality of care provided to the offspring [13][14][15][16][17], so we might expect the severity of inbreeding depression to be influenced by maternal traits such as body size, age, & 2016 The Author(s) Published by the Royal Society. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%